Foreign Body Reaction to a Subcutaneously Implanted Self-Cleaning, Thermoresponsive Hydrogel Membrane for Glucose Biosensors - Abraham, Alexander A. (ACS Biomater Sci Eng, 2018)
Towards achieveing a subcutaneously implanted glucose biosensor with long-term functionality, a thermoresponsive membrane previously shown to have potential to house a glucose sensing assay was evaluated herein for its ability to minimize the foriegn body reaction (FBR) and the resulting fibrous capsule. The severity of the FBR proportionally reduces diffusion of glucose to the sensor and hence sensor lifetime. However, efforts to reduce the FBR have largedly focused on anti-fouling materials that passively inhibit cellular attachment, particularly poly(ethylene glycol) (PEG). Herein, the extent of the FBR of a subcutaneously implanted “self-cleaning” cylindrical membrane was analyzed in rodents. This membrane represents an “actively anti-fouling” approach to reduce cellular adhesion. It is a thermoresponsive double network nanocomposite hydrogel (DNNC) comprised of poly(N-isopropylacrylamide) (PNIPAAm) and embedded polysiloxane nanoparticles. The membrane’s cyclical deswelling/reswelling response to local body temperature fluctuations was anticipated to limit cellular accumulation. Indeed, after 30 days, the self-cleaning membrane exhibited a notably thin fibrous capsule (~30 µm) and increased microvascular density within 1 mm of the implant surface in comparison to a non-thermoresponsive, benchmark biocompatible control (PEG diacrylate, PEG-DA)